A different approach to diagnosis of subclinical mastitis: milk arginase activity - Kandemir, Fatih M.; Yuksel, Murat; Ozdemir, Necmi; Deveci, Huseyin (Univ Zagreb Vet Faculty, 2013)
The aim of this study was to determine the relationships between subclinical mastitis and milk arginase activity in dairy cows. Thirty, various breed 4-8 year old cows from Firat University Animal Hospital were used in the study. Subclinical mastitis was diagnosed by the California Mastitis Test (CMT) combined with bacteriological examination of milk samples. The subclinical mastitis group consisted of fifteen clinically healthy but CMT and microbiologically positive animals. CMT and microbiologically negative animals (n = 15) served as the control group. Arginase activity in milk samples was measured by spectrophotometer using the thiocemicarbazide diacetylmonoxime urea (TDMU) method and protein was determined with the folin phenol reagent. Arginase activity in the milk of animals with subclinical mastitis (0.26 +/- 0.07 U/mg protein) significantly increased compared to the arginase activity in the milk from healthy animals in the control group (0.10 +/- 0.03 U/mg protein). Milk enzyme activity in the mildly severe disease (0.26 +/- 0.01 U/mg protein) was significantly lower than in the moderately severe disease (0.30 +/- 0.01 U/mg). No relationship was found between the nature of the bacterial infection of the cows with subclinical mastitis and their milk arginase activity. It was concluded that assay of milk arginase activity may be used as an additional laboratory method for the diagnosis of subclinical mastitis.
Dijagnostika supklini?kog mastitisa zasnovana na aktivnosti arginaze u mlijeku
Keywords: subclinical mastitis; arginase; cow; California mastitis test